Edukasi kesehatan untuk membangun kesadaran tentang pernikahan dini pada remaja - Pratama, Rika Yuanita; Sohibun, Sohibun; Wagiran, Wagiran; Karlia, Lilis (JOURNAL of Public Health Concerns, 2026)
Background: Early marriage among adolescents remains a public health problem in Indonesia due to its impact on reproductive health, maternal and child health, and psychosocial well-being. Adolescents' limited knowledge about the health risks of early marriage contributes to low awareness and attitudes toward delaying marriage. Schools are a strategic setting for implementing health promotion and preventive education for adolescents. Purpose: To increase adolescents' knowledge and awareness about early marriage from a health perspective. Method: This community service activity was conducted at SMA Negeri 4 Sintang on July 22, 2025, and involved 50 high school students as respondents. The activity implemented a community education approach through health counseling activities. Material was delivered through interactive lectures and discussions, accompanied by educational media in the form of visual presentations related to early marriage and adolescent reproductive health. The activity was evaluated using pre-test and post-test questionnaires, analyzed using Wilcoxon Signed Rank to measure changes in students' knowledge and awareness levels before and after the education. The data obtained were analyzed descriptively to illustrate differences in adolescents' knowledge and awareness levels regarding early marriage from a health perspective. Results: The results of the activity showed an increase in student knowledge and awareness after the education. Before the education (pre-test), the majority of students had poor knowledge regarding the health impacts of early marriage, amounting to 22 students (44.0%). After the intervention (post-test), the proportion of students with good knowledge increased to 25 students (50.0%), and the proportion with fair knowledge increased to 20 students (40.0%). This indicates an increase in students' understanding of reproductive health risks and the importance of delaying marriage until physical, psychological, and social readiness is achieved. Conclusion: Community service activities in the form of education on early marriage from a health perspective have proven effective in increasing adolescents' knowledge and awareness of the long-term impacts of early marriage. Suggestion: Education on early marriage from a health perspective needs to be carried out sustainably and integrated into school health promotion activities. Schools are expected to collaborate with health workers in providing comprehensive reproductive health education to students. Keywords: Adolescents; Early marriage Health education; Health promotion; Reproductive health Pendahuluan: Pernikahan dini pada remaja masih menjadi permasalahan kesehatan masyarakat di Indonesia karena berdampak pada kesehatan reproduksi, kesehatan ibu dan anak, serta kesejahteraan psikososial. Rendahnya pengetahuan remaja mengenai risiko kesehatan pernikahan dini berkontribusi terhadap rendahnya kesadaran dan sikap dalam menunda usia pernikahan. Sekolah merupakan setting strategis dalam pelaksanaan promosi kesehatan dan edukasi preventif bagi remaja. Tujuan: Untuk meningkatkan pengetahuan dan kesadaran remaja mengenai pernikahan dini dalam perspektif kesehatan. Metode: Kegiatan pengabdian kepada masyarakat ini dilaksanakan di SMA Negeri 4 Sintang pada tanggal 22 Juli 2025 dan melibatkan 50 siswa/siswi SMA untuk menjadi responden. Pelaksanaan kegiatan menggunakan pendekatan pendidikan masyarakat (community education) melalui kegiatan penyuluhan kesehatan. Materi disampaikan melalui ceramah interaktif dan diskusi, disertai media edukatif berupa presentasi visual yang berkaitan dengan pernikahan dini dan kesehatan reproduksi remaja. Evaluasi kegiatan dilakukan menggunakan instrumen kuesioner pre-test dan post-test yang dianalisis dengan Wilcoxon Signed Rank untuk mengukur perubahan tingkat pengetahuan dan kesadaran siswa sebelum dan sesudah diberikan edukasi. Data yang diperoleh dianalisis secara deskriptif untuk menggambarkan perbedaan tingkat pengetahuan dan kesadaran remaja terkait pernikahan dini dari perspektif kesehatan. Hasil: Hasil kegiatan menunjukkan adanya peningkatan pengetahuan dan kesadaran siswa setelah diberikan edukasi. Sebelum penyuluhan (pre-test), mayoritas siswa memiliki tingkat pengetahuan kurang mengenai dampak kesehatan pernikahan dini, yaitu sebanyak 22 siswa/siswi (44.0%). Setelah intervensi (post-test), proporsi siswa dengan tingkat pengetahuan baik meningkat menjadi 25 siswa/siswi (50.0%) dan kategori cukup menjadi sebanyak 20 siswa/siswi (40.0%). Hal ini menunjukkan peningkatan pemahaman siswa mengenai risiko kesehatan reproduksi serta pentingnya menunda pernikahan hingga kesiapan fisik, psikologis, dan sosial. Simpulan: Kegiatan pengabdian kepada masyarakat berupa edukasi pernikahan dini dalam perspektif kesehatan terbukti efektif dalam meningkatkan pengetahuan dan kesadaran remaja terhadap dampak jangka panjang pernikahan dini. Saran: Edukasi pernikahan dini dalam perspektif kesehatan perlu dilakukan secara berkelanjutan dan terintegrasi dalam kegiatan promosi kesehatan sekolah. Pihak sekolah diharapkan dapat bekerja sama dengan tenaga kesehatan dalam memberikan pendidikan kesehatan reproduksi yang komprehensif kepada siswa.